National Occupational Skill Standards (NOSS) for construction industry : fixed ceiling assistant installer - level 1, fixed ceiling installer - level 2 - 2891 Lembaga Pembangunan Industri Pembinaan Malaysia; Malaysia. Majlis Latihan Vokasional Kebangsaan (Kuala Lumpur : CIDB Malaysia)
PSZJBL